Epigenetic Regulation of Lipid Metabolism in Neural Stem Cell Fate Decision - Syal, Charvi (Université d'Ottawa / University of Ottawa, 2019)
Bioactive lipids have emerged as prominent regulators of neural stem and progenitor cell (NPC) function under both physiological and pathological conditions. However, how lipid metabolism is regulated, and its role in modulation of NPC function remains unknown. In this regard, my study defines a novel epigenetic pathway that regulates lipid metabolism to determine NPC proliferation versus differentiation. Specifically, I show that activation of an atypical protein kinase C (aPKC)-mediated Ser436 phosphorylation of CREB binding protein (CBP) by aging, metformin stimulation and continued passaging in vitro, represses expression of monoacylglycerol lipase (Mgll) to promote neuronal differentiation of adult NPCs. Mgll, a lipase that hydrolyzes the endocannabinoid 2-arachidonoyl glycerol (2-AG) to produce arachidonic acid (ARA), is thus a key regulator of two critical bioactive lipid signaling pathways in the brain and a potential modulator of NPC function. I observed elevated Mgll levels, concomitant with neuronal differentiation deficits in both the lateral ventricle sub-ventricular zone (SVZ) and the hippocampal subgranular zone (SGZ) NPCs of phospho-null CBPS436A mice, that lack a functional aPKC-CBP pathway. Genetic knockdown of Mgll or inhibition of Mgll activity rescued these neuronal differentiation deficits. In addition, I found that CBPS436A SVZ NPCs exhibit enhanced proliferation at the expense of differentiation as an outcome of increased Mgll levels in culture. Interestingly, I also observed that SVZ NPCs from an Alzheimer’s disease (AD) model, the 3xTg mice, closely resemble CBPS436A NPC behaviour in culture. 3xTg NPCs exhibit attenuation of the aPKC-CBP pathway, which is associated with elevated Mgll expression and increased NPC proliferation at the expense of neuronal differentiation. Reactivation of the aPKC-CBP mediated-Mgll repression in 3xTg AD NPCs mitigates their differentiation deficits. These findings implicate Mgll as a critical switch that regulates NPC function by altering bioactive lipid signaling (2-AG versus ARA). They demonstrate that the aPKC-CBP mediated Mgll repression is essential for normal NPC function, and that when perturbed in AD, it causes impaired NPC function to generate fewer neurons, contributing to AD predisposition.
Keywords: Lipid Metabolism; Neural Stem Cell